Yield and physical characteristics of agar from Gracilaria fisheries at Setiu, Terengganu - Majanil Fredolin Peter (2014)
In commercial agar production from Gracilaria species, alkali pretreatment is usually done to improve the quality o f its agar. This study is to check whether G. fisheri from Setiu, Terengganu collected in June 1997 needed alkali pretreatment (5%) NaOH for 1.5 hour, acid treatment with 1.5% H2SO4 and if alkali treatment was necessary, determine its most appropriate treatment temperature (temperature tested:60, 70, 80 and 90 °C)